Connected & disconnected in Viet Nam : remaking social relations in a post-socialist nation - Taylor, Philip, 1962- (Vietnam series (Acton, A.C.T.), 2016)
Vietnam's shift to a market-based society has brought about profound realignments in its people's relations with each other. As the nation continues its retreat from the legacies of war and socialism, significant social rifts have emerged that divide citizens by class, region and ethnicity. By drawing on social connections as a traditional resource, Vietnamese are able to accumulate wealth, overcome marginalisation and achieve social mobility. However, such relationship-building strategies are also fraught with peril for they have the potential to entrench pre-existing social divisions and lead to new forms of disconnectedness. This book examines the dynamics of connection and disconnection in the lives of contemporary Vietnamese. It features 11 chapters by anthropologists who draw upon research in both highland and lowland contexts to shed light on social capital disparities, migration inequalities and the benefits and perils of gift exchange. The authors investigate ethnic minority networks, the politics of poverty, patriotic citizenship, and the 'heritagisation' of culture. Tracing shifts in how Vietnamese people relate to their consociates and others, the chapters elucidate the social legacies of socialism, nation-building and the transition to a globalised market-based economy. With compelling case studies and including many previously unheard perspectives, this book offers original insights into social ties and divisions among the modern Vietnamese.